Impacts of Ceftriaxone Exposure During Pregnancy on Maternal Gut and Placental Microbiota and Its Influence on Maternal and Offspring Immunity in Mice (OR01-04-19) - Cheng, Ruyue (Curr Dev Nutr, 2019)
OBJECTIVES: This study aimed to investigate whether antibiotic exposure during pregnancy could alter maternal gut and placental microbiota, and consequently affect the immunity of both mother and offspring. METHODS: Pregnant BALB/c mice (n = 24) were gavaged with ceftriaxone from gestation day 13 to delivery. Both dams and pups were then sacrificed immediately after delivery. Spleen, placental, and fecal samples were collected from the tested dams, and blood samples were collected from both the dams and their pups. The microbiota in the feces and placenta of the dams were comprehensively analyzed using16S rRNA sequencing. Furthermore, viable bacteria in the placentas of dams were also isolated by plate cultivation then taxonomically identified in detail by clone sequencing. Serum cytokines collected from dams and pups were quantitatively profiled using Luminex. RESULTS: The maternal spleen index was significantly lower and the offspring serum interleukin-6 (IL-6) levels were significantly higher in ceftriaxone-treated mice compared with the control group. The diversity of maternal fecal microbiota was significantly lower in ceftriaxone-treated mice. The relative abundance of Bacteriodetes was significantly lower, while the relative abundance of Tenericutes was significantly higher in ceftriaxone-treated mothers. However, no significant differences in placental microbiota communities or metagenomic activity were found between the control group and the ceftriaxone-treated mice. CONCLUSIONS: These results indicated that ceftriaxone exposure in pregnancy could dramatically alter maternal intestinal microbiota, which affected the immunity of the mothers and their offspring, characteristically by enhanced pro-inflammatory responses. The results from the present study also indicated that the placenta might harbor its own microbes, which may not be affected by environmental factors, such as oral administration of ceftriaxone during pregnancy. Further studies should be focused on the role of these microbes in the health of the fetus and infants. FUNDING SOURCES: This work was supported by the National Natural Science Foundation of China (Grant number 81372982).